MEANS AND METHODS OF SPECIFIC PREVENTION OF PIGS’ MYCOPLASMOSIS - Бердник, В. П.; Бублик, О. О.; Бердник, І. Ю.; Щербак, В. І. (Scientific Progress & Innovations, 2015)
The article is devoted to the study of specific prevention methods of pigs’ mycoplasmosis in Ukraine. The results of numerous studies show that in farms of Ukraine M. hyorhinis, M. arginini, M. hyosynoviae i, rarely, M. hyopneumoniae and Acholeplasma (A.) laidlawii are the most frequently exciter of pigs’ mycoplasmosis (PM). It turns out that the vaccine must be prepared using strains of these species of mycoplasma and aholeplasma. The use of inactivated vaccines of exciter has much lower efficiency compared to not inactivated vaccines that are injected into the respiratory ways.